2022
DOI: 10.1371/journal.pone.0269554
|View full text |Cite
|
Sign up to set email alerts
|

Identification of four serum miRNAs as potential markers to screen for thirteen cancer types

Abstract: Introduction Cancer consistently remains one of the top causes of death in the United States every year, with many cancer deaths preventable if detected early. Circulating serum miRNAs are a promising, minimally invasive supplement or even an alternative to many current screening procedures. Many studies have shown that different serum miRNAs can discriminate healthy individuals from those with certain types of cancer. Although many of those miRNAs are often reported to be significant in one cancer type, they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Figure 5 presents the common miRNAs between two related studies ( 18 , 21 ) and miRNAs that were obtained in our study. There is some evidence in the literature for the biomarkers included in our study.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Figure 5 presents the common miRNAs between two related studies ( 18 , 21 ) and miRNAs that were obtained in our study. There is some evidence in the literature for the biomarkers included in our study.…”
Section: Discussionmentioning
confidence: 92%
“…Jeon et al ( 17 ) reported that the serum and tissue miR-1290 was significantly elevated in patients with epithelial ovarian cancer compared with patients with benign ovarian neoplasm. Chen et al ( 18 ) reported a total of 19 miRNAs, which were identified by random forest models, that were important in cancer diagnosis. In this study, the top five miRNAs with the highest frequency were chosen to be the biomarker candidates for cancer screening, which has-miR-3184-5p achieved a high rank.…”
Section: Introductionmentioning
confidence: 99%
“…The miRNA of has-miR-3127-5p regulating the target key genes of tumor mutation burden (TMB), has a potential effect on the therapeutic responses in cancers 28 . In addition, serum has-miR-3184-5p was predicted as a diagnosis biomarker for multiple cancer types 29 . Both miRNAs have not been identified with spermatogenesis or testis development yet.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, a pre-printed article trains serum samples of 13 cancers (including OVC) and non-cancer serum samples and identifies a set of serum pan-cancer biomarkers consisting of five miRNAs ( 26 ). We found that one of the selected miRNAs, miR-6784-5p, is also included in our 13-miRPairs classifier, indicating the pan-cancer predictive ability of this miRNA.…”
Section: Discussionmentioning
confidence: 99%